(untitled) (Biological Sciences - PJSIR, 1998)
This paper presents a kinetic study of the leaching of iron and magnesium impurities from rock phosphate with hydrochloric acid.The effects of particle size, stirring speed,hydrochloric acidconcentration andreaction tempera- ture on the leaching rate were investigated. The data fitted a shrinking core model equation with reaction rate controlled by a diffusion mechanism. The rate was related to temperature by the Arrhenius relationship with the apparent activation energy being 18. 7kJ mol" for iron and 14.3kJ mol’1 for magnesium. The rate was linearly dependent onhydrochloric acidconcentrationandinverselyproportionaltotheaveragediameteroftheparticles.The leachingrateofmagnesiumwasrelativelyfasterthanthatofironbutbothexhibitedsimilarleachingpatternunder the same reactionconditions.